Embryogenesis of esophageal atresia: Is localized vascular accident a factor? - Dutta Hemonta; Harsh Shree (Wolters Kluwer Medknow Publications, 2009)
Several theories on embryogenesis of esophageal atresia have been proposed, none could explain the whole spectrum of this anomaly. We report a new variant of esophageal atresia in which the two blind pouches were joined by an atretic band. Histology of the atretic part showed groups of striated muscle arranged haphazardly without any lumen. The existing theories on etiology of esophageal atresia cannot explain this variant. However, localized vascular accident during intrauterine life resulting in disturbances in regional microcirculation could be a possible factor as demonstrated by Louw and Barnard in relation to jejunoileal atresia. This is contrary to the current understanding that disproportionate growth of the horizontal esophageal folds results in esophageal atresia.